NEW PERSPECTIVE IN THE LEADERSHIP VALUES BASED ON BUGIS CULTURES IN “P” RESTAURANT - Jerry Rudi Lamat; Wiyono Pontjoharyo; Noviaty Kresna Darmasetiawan (CALYPTRA, 2021)
Abstract Purpose This study aims to explore the Bugis leadership values in the small business “P” restaurant. The factors under study that are the Bugis values, SMEs, and the leadership values. Design / methodology / approach Semi-structured interviews and observations are used to collect the research data. “P” restaurant owner asked to explain the culture in the restaurant when the owner led the restaurant. Employees are asked to assess their leaders regarding perceptions about the characteristics of their leaders. Findings The results showed that the theory of cultural leadership can be applied in Indonesia. In this case the culture of leadership can be associated with leadership values Originality This research applies the value of Bugis culture in "P" restaurant as an effort to find out the appropriate leadership values factors based on culture, where Bugis culture and leadership values are the most important factors in determining the right leadership for effectiveness in a SMEs. Keywords: bugis culture, leadership, values, SMEs. Abstrak Tujuan Penelitian ini bertujuan untuk mengeksplorasi nilai-nilai kepemimpinan Bugis di restoran "P" bisnis kecil. Faktor-faktor yang diteliti adalah nilai-nilai Bugis, UKM, dan nilai kepemimpinan. Desain / metodologi / pendekatan Wawancara dan observasi semi-terstruktur digunakan untuk mengumpulkan data penelitian. Pemilik restoran “P” diminta menjelaskan budaya di restoran ketika pemilik memimpin restoran. Karyawan diminta menilai pemimpin mereka tentang persepsi mereka tentang karakteristik pemimpin mereka. Temuan Hasil penelitian menunjukkan bahwa teori kepemimpinan budaya dapat diterapkan di Indonesia. Dalam hal ini budaya kepemimpinan dapat dikaitkan dengan nilai-nilai kepemimpinan. Orisinalitas Penelitian ini menerapkan nilai budaya Bugis di restoran "P" sebagai upaya untuk mengetahui faktor gaya kepemimpinan yang tepat berdasarkan budaya, di mana budaya Bugis dan nilai kepemimpinan adalah faktor paling penting dalam menentukan kepemimpinan yang tepat untuk efektivitas dalam UKM. Kata kunci: budaya bugis, kepemimpinan, nilai, UKM.